The State of the Art in Inducing PVY Resistance into Potato Cultivars by Biotechnological Methods - AURORI, Adriana; BĂDĂRĂU, Carmen; RAKOSY-TICAN, Elena (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Inducing resistance to pathogens in different crops was a continuous concern of the researchers and several biotechnological methods have been developed. Due to its high economic importance, potato raised a huge interest in developing such researches and having a significant contribution in refining of several methods. One of the most threatening pathogen of potato is represented by potato virus Y (PVY), this being able to jeopardize up to 80% of the crop yield. The high variability of PVY, as a result of naturally raised mutations or recombination was a continuous challenge, very often leading to overcoming the resistance of different potato cultivars. Today potato virus Y has a high genetic variability with a significant number of strains: PVY0, PVYC, PVYZ, PVYN, PVYNTN, and PVYN-W. The last two strains: PVYNTN (N-tuber-necrosis) and PVYN-W (N-Wilga) have a rapid spread and produce Potato Tuber Necrotic Ringspot Disease (PTNRD), affecting both leaves and tubers, and hence producing very height yield loses.